Wisconsin Public Library System Standards. Bulletin No. 5058 - Wisconsin State Dept. of Public Instruction, Madison. Div. of Library Services; Wisconsin State Dept. of Public Instruction, Madison. Div. of Library Services ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
A revision of the Wisconsin Division for Library Services of the Department of Public Instruction 1963 public library standards, this collection of standards includes sections on availability of services, structure and government of library systems, services, materials and materials organization, personnel, physical facilities, and library service outlets. Except for the last section, which is a short description, all sections have a narrative introduction, statements of guide principles, and specific standards. The standards, which are presented in column form, cover library systems, headquarters libraries, large community libraries, community libraries, and small community libraries. These five types of library organizations are defined at the beginning of the document in terms of population served. (LS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: County Libraries; Information Services; Institutional Administration; Library Facilities; Library Materials; Library Services; Library Standards; Personnel; Public Libraries; Regional Libraries; State Standards; Wisconsin; Books